Perceptions of Portuguese parents about the acceptability of a multicomponent intervention targeted at behavioral inhibition during early childhood. Issue 2 (8th December 2020) - Guedes, Maryse; Matos, Inês; Almeida, Telma; Freitas, Miguel; Alves, Stephanie; Santos, António J.; Verissimo, Manuela; Chronis‐Tuscano, Andrea; Rubin, Kenneth H.
ABSTRACT: High and stable behavioral inhibition during early childhood is a risk factor for later anxiety disorders. The few available interventions targeted at behavioral inhibition have not yet been implemented in European countries. Evaluating intervention acceptability is essential when introducing interventions in new cultures. This study aimed to explore the perceptions of parents about the acceptability of the multicomponent Turtle Program in Portugal. Participants were 12 parents (from seven families) of children with a positive screening on the Behavioral Inhibition Questionnaire and no diagnoses of developmental disorders/selective mutism. Children's mean age was 55.86 months and most children were female and first‐born. Parents and children participated in the eight‐sessions Turtle Program. After each session, parents completed weekly satisfaction checklists. Following completion of the full intervention, parents were invited to participate in individual qualitative in‐depth interviews. The thematic analysis revealed that both parents perceived the intervention objectives and contents as relevant. Both parents suggested the introduction of follow‐up sessions, the discussion of practical experiences, the need to be sensitive to cultural differences in positive language, and the provision of more feedback about children's activities. These findings support prior research on the acceptability and cultural tailoring needed for parenting and child socioemotional learning interventions. RESUMEN: Una alta y estable conducta de inhibición durante la temprana niñez es un factor de riesgo para posteriores trastornos de ansiedad. Las pocas intervenciones disponibles que se enfocan en la inhibición de la conducta no se han implementado aún en países europeos. Evaluar el nivel de aceptación de la intervención es esencial cuando las intervenciones se introducen en nuevas culturas. Este estudio se propuso explorar las percepciones de los progenitores acerca del nivel de aceptación del multi‐compuesto Programa Tortuga en Portugal. Los participantes fueron 12 progenitores (de siete familias) de niños con una positiva detección en el Cuestionario de Inhibición de la Conducta y sin diagnóstico de trastornos de desarrollo/mutismo selectivo. La edad promedio de los niños fue 55.86 meses y la mayoría eran niñas y primogénitas. Los progenitores y los niños participaron en las ocho sesiones del Programa Tortuga. Después de cada sesión, los progenitores completaron listas semanales de chequeo de la satisfacción. Luego de completar la intervención en su totalidad, se invitó a los progenitores a participar en entrevistas cualitativas individuales para profundizar. Los análisis temáticos revelaron que ambos progenitores percibieron como relevantes los objetivos y el contenido de la intervención. Ambos progenitores sugirieron introducir sesiones de seguimiento, la discusión de experiencias prácticas, la necesidad de mostrarse sensible a las diferencias culturales en lenguaje positivo y la provisión de más información sobre las actividades de los niños. Estos resultados apoyan la investigación anterior sobre el nivel de aceptación y la adaptación cultural necesarias en las intervenciones sobre la crianza y el aprendizaje socioemocional del niño. RÉSUMÉ: L'inhibition comportementale élevée et stable durant la petite enfance est un facteur de risque pour des troubles de l'anxiété plus tard. Quelques interventions disponibles ciblant l'inhibition comportementale n'ont pas encore été mises en œuvre dans les pays européens. Evaluer l'acceptabilité de l'intervention est essentiel lorsqu'on introduit des interventions dans de nouvelles cultures. Cette étude s'est donnée pour but d'explorer les perceptions des parents à propos de l'acceptabilité du Programme Tortue à composants multiples au Portugal. Les participants ont consisté en 12 parents (de sept familles) d'enfants ayant eu un dépistage positif au Questionnaire d'Inhibition Comportementale et aucun diagnostic de troubles développementaux / mutisme sélectif. L'âge moyen des enfants était de 55, 86 mois et la plupart des enfants étaient des filles et des premières nées. Les parents et les enfants ont participé au Programme Tortue de huit séances. Après chaque séance les parents ont rempli des checklists de satisfaction hebdomadaires. Après avoir terminé l'intervention totale les parents ont été invité à participer à des entretiens individuels en profondeur et qualitatifs. L'analyse thématique a révélé que les deux parents percevaient les objectifs d'intervention et les contenus comme étant pertinents. Les deux parents ont suggéré l'introduction de séances de suivi, la discussion d'expériences pratiques, le besoin d'être sensible aux différences culturelles dans le langage positif et le besoin de plus de commentaires sur les activités des enfants. Ces résultats soutiennent les recherches précédentes sur l'acceptabilité et l'adaptation culturelle nécessaire pour le parentage et les interventions pour le développement socioémotionnel de l'enfant. ZUSAMMENFASSUNG: Wahrnehmung portugiesischer Eltern hinsichtlich der Akzeptanz einer Mehrkomponentenintervention zur Verhaltensinhibition in der frühen Kindheit Eine hohe und stabile Verhaltensinhibition in der frühen Kindheit ist ein Risikofaktor für spätere Angststörungen. Die wenigen verfügbaren Interventionen zu Verhaltensinhibition wurden in europäischen Ländern noch nicht implementiert. Wenn Interventionen in neue Kulturkreise eingeführt werden sollen, ist es wichtig, deren Akzeptanz zu evaluieren. Ziel dieser Studie war es, die elterliche Wahrnehmung hinsichtlich der Akzeptanz des Mehrkomponenten‐Schildkrötenprogramms in Portugal zu untersuchen. 12 Elternteile (aus sieben Familien) von Kindern mit einem positiven Screening auf den Fragebogen zur Verhaltensinhibition und ohne Diagnose von Entwicklungsstörungen / selektivem Mutismus nahmen an der Studie teil. Das Durchschnittsalter der Kinder betrug 55, 86 Monate und die meisten Kinder waren weiblich und erstgeboren. Eltern und Kinder nahmen an acht Sitzungen des Schildkröten‐Programms teil. Nach jeder Sitzung füllten die Eltern wöchentliche Zufriedenheitschecklisten aus. Nach Abschluss der vollständigen Intervention wurden die Eltern eingeladen, an individuellen qualitativen Tiefeninterviews teilzunehmen. Die thematische Analyse ergab, dass beide Elternteile die Interventionsziele und ‐inhalte als relevant empfanden. Beide Elternteile schlugen eine Einführung von Follow‐up‐Sitzungen, eine Diskussion praktischer Erfahrungen, die Notwendigkeit, auf kulturelle Unterschiede in der positiven Sprache zu achten, und mehr Feedback zu den Aktivitäten der Kinder zu geben, vor. Diese Ergebnisse stützen bisherige Forschungsarbeiten zur Akzeptanz und kulturellen Anpassung, die für sozioemotionale Lerninterventionen von Eltern und Kindern erforderlich sind. 抄録: 乳幼児期における行動抑制を対象とした複数構成要素からなる介入への受容性に ついてのポルトガル人両親の認識 乳幼児期の行動抑制が高い割合で変化することなく生じている時、それは後の不 安障害の危険因子となる。行動抑制を対象としたいくつかの利用可能な介入は、 ヨーロッパ諸国ではまだ実施されていない。新しい文化において介入を導入する 場合、その介入の受容性を評価することが不可欠である。本研究は、ポルトガル における複数構成要素からなるTurtle Programの受容性についての両親の認識を 調査することを目的とした。参加者は、行動抑制質問紙で陽性のスクリーニング を受け、発達障害/場面緘黙症の診断を受けていない子どもの (7家族からの) 12 人の親であった。子どもの平均年齢は55.86ヶ月で、ほとんどの子どもは女子で 長子であった。親子で8セッションのTurtle Programに参加した。各セッション 後、両親は満足度チェックリストに毎週答えた。全ての介入の完了後、両親は質 的で詳細なインタビューを受けることを勧められた。主題分析により、両親は介 入の目的と内容が適切であると認識していることが明らかとなった。両親は共に、 フォローアップセッションの紹介、実践的な体験の議論、肯定的な言葉を使って 文化の違いに繊細であることの必要性、そして子どもたちの活動についてのより 多くのフィードバックの提供、を提案した。これらの調査結果は、子育て及び子 どもの社会情緒的な学習介入に必要な受容性と文化的な調整に関する先行研究を 支持する。 摘要: 幼儿期明显而持续的行为抑制是未来焦虑症的一个危险因素。欧洲国家尚未实施针对行为抑制的少数可用干预措施。在新文化中引入干预措施时, 评估干预措施的可接受性是至关重要的。本研究旨在探讨葡萄牙家长对多因素"海龟计划"可接受性的看法。参与者为12名 (来自7个家庭) 行为抑制问卷筛查阳性, 且未诊断为发育障碍或选择性缄默症的儿童家长。儿童的平均年龄为55.86个月, 且多为女性和头胎。父母和儿童参与了八期"海龟计划"。每期干预结束后, 父母都要填写每周的满意度检查清单。在完成全面干预后, 父母被邀请参加个性化的深入访谈。主题分析显示, 父母双方都认为干预目标和内容是相关的。父母双方都建议采取跟进干预活动, 讨论实践经验, 需要对正面语言中的文化差异保持敏感, 并提供更多关于儿童活动的反馈意见。这些发现支持了先前对育儿和儿童社会情感学习干预所需的可接受性和文化适应性的研究。 ملخص: تصورات الآباء والأمهات البرتغاليين حول قبول تدخل متعدد المكونات يستهدف الكبت السلوكي خلال مرحلة الطفولة المبكرة الكبت السلوكي خلال مرحلة الطفولة المبكرة هو عامل خطر يؤدي لاضطرابات القلق في وقت لاحق. ولم تنفذ بعد في البلدان الأوروبية التدخلات القليلة المتاحة التي تستهدف الكبت السلوكي. إن تقييم مقبولية التدخل أمر ضروري عند إدخال التدخلات في الثقافات الجديدة. تهدف هذه الدراسة إلى استكشاف تصورات الآباء والأمهات حول قبول برنامج Turtle متعدد المكونات في البرتغال. وكان المشاركون 12 من الآباء والأمهات (من سبع عائلات) وأطفالهم الذين أظهروا نتيجة إيجابية على استبيان الكبت السلوكي ولم يتم تشخيصهم باضطرابات النمو. وكان متوسط عمر الأطفال 655.8 شهراً، ومعظم الأطفال كانوا من الإناث. شارك الآباء والأطفال في برنامج Turtle الذي امتد ثماني جلسات. وبعد كل جلسة، أكمل الآباء قوائم التحقق الأسبوع عن القبول والرضا. وبعد الانتهاء من التدخل الكامل، دُعي الآباء إلى المشاركة في مقابلات فردية متعمقة نوعية. وكشف التحليل المواضيعي أن كلا الوالدين كانا يعتبران أهداف التدخل ومحتوياته ذات صلة بهم. واقترح الوالدان إدخال جلسات متابعة، ومناقشة التجارب العملية، وضرورة مراعاة الاختلافات الثقافية من خلال استخدام لغة إيجابية، وتقديم مزيد من المعلومات عن أنشطة الأطفال. وتدعم هذه النتائج البحوث السابقة بشأن المقبولية والتكييف الثقافي اللازمين لتدخلات التنشئة الأبوية والتعلم الاجتماعي العاطفي للأطفال.